(untitled) (Research, Society and Development, 2020)
Objective: to know the experience of couples in the puerperal period about the partner’s participation. Method: descriptive qualitative research, performed through semi-structured interview and the “Almanac” Creativity and Sensitivity Technique. The data were analyzed according to the operational proposal. The study population consisted of ten couples who were experiencing the immediate, late or remote puerperium. Results: they were organized in a category called “the couple’s daily life in the puerperium: changes and active participation of the partner”. Each couple experienced the puerperium according to their uniqueness, adapting their routine and reorganizing it. The partners who were included in the puerperium felt more satisfied when carrying out the care with the baby. Conclusion: The active participation of the partners contributed significantly to the couples experiencing this period with more satisfaction, strengthening the father-mother-child bond.